2021
DOI: 10.3390/math9121353
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Three-Term Conjugate Gradient Algorithm for Large-Scale Unconstrained Problems

Abstract: Three-term conjugate gradient methods have attracted much attention for large-scale unconstrained problems in recent years, since they have attractive practical factors such as simple computation, low memory requirement, better descent property and strong global convergence property. In this paper, a hybrid three-term conjugate gradient algorithm is proposed and it owns a sufficient descent property, independent of any line search technique. Under some mild conditions, the proposed method is globally convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Tian et al [56] suggested a new hybrid three-term CG approach without using a line search method. The authors of [56] designed the new hybrid descent three-term direction in the following form:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [56] suggested a new hybrid three-term CG approach without using a line search method. The authors of [56] designed the new hybrid descent three-term direction in the following form:…”
Section: Introductionmentioning
confidence: 99%
“…They proceeded to provide some remarks regarding their proposed directions. In addition, the authors of [56] successfully performed a convergence analysis of their newly proposed CG method (under certain conditions). The numerical outcomes demonstrate that the three-term CG method is more efficient and reliable in terms of solving large-scale unconstrained optimization problems compared to other methods.…”
Section: Introductionmentioning
confidence: 99%